Methodology to assess drivers of vegetables intake in urban Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The methodology was published in 2018 and informed the development of an intervention called “Veggies on Wheels” that was tested in urban Nigeria. The methodology, along with results from the evaluation, are being used to develop another intervention that will be tested in Lagos.